2017
DOI: 10.1111/1440-1681.12863
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent electrocardiographic changes in Pgc‐1β deficient murine hearts

Abstract: SummaryIncreasing evidence implicates chronic energetic dysfunction in human cardiac arrhythmias. Mitochondrial impairment through Pgc‐1β knockout is known to produce a murine arrhythmic phenotype. However, the cumulative effect of this with advancing age and its electrocardiographic basis have not been previously studied. Young (12‐16 weeks) and aged (>52 weeks), wild type (WT) (n = 5 and 8) and Pgc‐1β−/− (n = 9 and 6), mice were anaesthetised and used for electrocardiographic (ECG) recordings. Time intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…The peroxisome proliferator-activated receptor (PPAR) gamma coactivator-1 (PGC-1) family of transcriptional coactivators, mainly including PGC-1α and PGC-1β, have emerged as being major regulators of mitochondrial biogenesis and cellular metabolism to regulate the cellular bioenergetics [4,5]. The members of PGC-1 family are multifunctional transcriptional co-regulators that take on "molecular switches" in many physiological and pathological processes [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peroxisome proliferator-activated receptor (PPAR) gamma coactivator-1 (PGC-1) family of transcriptional coactivators, mainly including PGC-1α and PGC-1β, have emerged as being major regulators of mitochondrial biogenesis and cellular metabolism to regulate the cellular bioenergetics [4,5]. The members of PGC-1 family are multifunctional transcriptional co-regulators that take on "molecular switches" in many physiological and pathological processes [6].…”
Section: Introductionmentioning
confidence: 99%
“…They are highly expressed in oxidative capacity and energy demanding tissues, such as heart, brain, skeletal muscle and brown adipose tissue [7][8][9][10] and considered to be essential for many of exercise response in skeletal muscle [11]. Specifically, PGC-1α and PGC-1β can interact with each other, or interact with multiple transcription factors, such as forkhead/winged helix protein family member FOXO1, and nuclear respiratory factor-1/2 (NRF1/2) in tissue specific manner [5,12] to modulate in mitochondrial biogenesis, fatty acid β-oxidation, adipogenesis, adaptive thermogenesis and tricarboxylic acid cycle [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Recent electrocardiographic studies reported age-dependent slowing of myocardial action potential (AP) conduction in Pgc-1β −/− hearts ( Ahmad et al, 2017 ). Intracellular recording studies then reported age-dependent atrial arrhythmic phenotypes associated with the AP conduction abnormalities in intact Langendorff perfused Pgc-1β −/− hearts ( Valli et al, 2017 ) agreeing with previous reports on their pro-arrhythmic ventricular phenotypes ( Gurung et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although murine hearts show anatomical differences, have higher pacing rates and shorter APs compared to human hearts, they have been established to substantially recapitulate human clinical arrhythmic phenotypes [ 20 , 21 ]. Previous studies have successfully validated both Pgc-1α −/− and Pgc-1β −/− murine models in the study of mitochondrial dysfunction and arrhythmogenesis [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, at a cellular level, extensive loose patch clamp studies implicated reduced Na + currents but unchanged K + currents as a factor for the previously determined slowed conduction velocity in Pgc-1β −/− atria [ 28 ]. At a systems level, electrocardiographic (ECG) studies in these mice have shown irregular PR, PP and RR intervals with differing P wave morphologies as well as reduced atrioventricular node (AVN) function following adrenergic stimulation [ 23 , 24 ]. Interestingly, murine studies of Pgc-1α −/− overexpression have shown changes in Ca 2+ signalling, electrophysiology, and contractile properties [ 25 ].…”
Section: Introductionmentioning
confidence: 99%